SEVICIA (PHYSICAL ABUSE) AND LEGAL LAWSUIT LIKE EXAMPLES OF DOMINATION AND RESISTANCE BETWEEN OWNERS AND BLACK SLAVES IN THE SANTIAGO, LATE COLONIAL PERIOD. THE CASE OF THE SLAVE THADEA ARANGUEZ, 1775-1776. - Duarte Sepúlveda, Natalia (Revista de Historia Social y de las Mentalidades, 2024)
The present article invites us to bring us over to the topic to the study of the sevicia - use of the excessive violence on the part of the owners - as element of colonial domination, exercised on the black slaves in the city of Santiago in the second half of the 18th century. Together with it, the reaction of the subjects dominated often is far from a passive and submissive attitude. These demonstrate a rejection to the domination imposed by means of different ways, there being constituted what is named a resistance. The slave, on having taken knowledge of his juridical condition, uses the legal lawsuit as a specific way of resistance opposite to the domination. The juridical practice is a resource that the secondary subjects use during the colonial studied epoch, with the aim of reclaim essential prerogatives and to face to the estigmatización and prejudices with those who were loading the above mentioned subjects in a scene of deep social differentiations.